The leading brain : powerful science-based strategies for achieving peak performance - Fabritius, Friederike; Hagemann, Hans Werner, 1959- (New York, New York : TarcherPerigee, an imprint of Penguin Random House LLC, 2017)
'Combining their expertise in both neuropsychology and management consulting, neuropsychologist Friederike Fabritius and leadership expert Dr. Hans W. Hagemann present simple yet powerful strategies for sharpening focus, achieving the highest performance, learning and retaining information more efficiently, improving complex decision-making, and cultivating trust and building strong teams' -- Provided by publisher.
Introduction: the science of leadership -- Find your sweet spot -- Regulate your emotions -- Sharpen your focus -- Manage habits -- Unleash your unconscious -- Foster learning -- Thrive on diversity -- Cultivate trust -- Develop the team of the future -- Final note: keeping the brain in mind.
Includes bibliographical references (pages 285-304) and index.
Keywords: Leadership -- Psychological aspects; Performance -- Psychological aspects; BUSINESS & ECONOMICS -- Personal Success; PSYCHOLOGY -- Cognitive Neuroscience & Cognitive Neuropsychology; BUSINESS & ECONOMICS -- Motivational